2019
DOI: 10.3389/fimmu.2019.01901
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Extracellular Vesicles as Carriers of Alarmins and Their Potential Involvement in Bone Homeostasis

Abstract: Extracellular vesicles are a heterogeneous group of cell-derived membranous structures, which facilitate intercellular communication. Recent studies have highlighted the importance of extracellular vesicles in bone homeostasis, as mediators of crosstalk between different bone-resident cells. Osteoblasts and osteoclasts are capable of releasing various types of extracellular vesicles that promote both osteogenesis, as well as, osteoclastogenesis, maintaining bone homeostasis. However, the contribution of immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 93 publications
2
37
0
Order By: Relevance
“…A growing body of evidence has highlighted the importance of exosomes for macrophage biology under both homeostatic and pathological circumstances. Macrophage derived exosomes are involved in maintaining bone homeostasis (18). In tumor microenvironment, exosomes derived from tumor associated macrophages (TAMs) have been proven to promote migration and invasion of colorectal cancer cells and to regulate aerobic glycolysis of breast cancer cells, via transferring certain miRNAs or lncRNAs, respectively (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence has highlighted the importance of exosomes for macrophage biology under both homeostatic and pathological circumstances. Macrophage derived exosomes are involved in maintaining bone homeostasis (18). In tumor microenvironment, exosomes derived from tumor associated macrophages (TAMs) have been proven to promote migration and invasion of colorectal cancer cells and to regulate aerobic glycolysis of breast cancer cells, via transferring certain miRNAs or lncRNAs, respectively (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…For example, monocyte-derived EVs shuttle miR-155 to the endothelium, increasing endothelial cell migration [98]. Lv et al demonstrated that vesicular tubular epithelial cells communicate by EVs shuttling miR-19b-3p to macrophages, leading to M1 Interestingly, all the resident bone cells, i.e., osteoblasts, monocytes/macrophages, osteoclasts, osteocytes, adipocytes, and endothelial cells, have been demonstrated to release EVs or respond to EVs both in physiological and pathological conditions [89][90][91][92][93][94][95][96]. EVs have been identified to shuttle molecules coming from the molecular legacy of the donor cells, exerting a specific effect according to the metabolic status of parental cells [97].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…In contrast, activated OMCs including proinflammatory M1 and anti-inflammatory M2 ( 13 ) may migrate from centers of erythropoiesis in the erythroblastic islands coincidental with the reticular niches of the central and perisinusoidal BM ( 14 , 15 ) to the endosteal and subendosteal BM (i.e., tissue adjacent to main bulk of BM), to support myelopoiesis from hemopoietic stem cells (HSCs) and uncommitted progenitors ( 16 ). Therefore, an inflammatory trigger pushes monocytes and OMCs toward opposite directions inside the BM.…”
Section: Microtopography Of Immune Cells In Bone Compartmentsmentioning
confidence: 99%
“…As a result, OMCs secrete IL-1ÎČ, IL-6, and tumor necrosis factor (TNF) α catalizing differentiation of pre-OCs to functionally competent OCs, thus inducing bone resorption ( 30 – 32 ). A further level of OCs activation by M1 is provided through release of extracellular microvesicles containing histones ( 13 ). It is therefore expected that primary sites of lesion ensuing from action of OMCs are the trabecular subendosteal bone and internal free edge of the lamellae in the cortical case, only later involving the periosteal surface.…”
Section: Key Points On Immunobiology Of Bone Remodeling Relevant To Tmentioning
confidence: 99%